A Novel Method for 3-D Building Structure Determination in Through-the-Wall Radar - Qichang Guo; Xingdong Liang; Yanlei Li (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Three-dimensional (3-D) through-the-wall imaging is a challenging topic. It has attracted some research attention in recent years. The 3-D structure is hard to reconstruct because of the limited measurement in the computerized tomography (CT)-mode imaging method. In order to obtain an accurate 3-D result, the 3-D total variation (3-D TV) algorithm has been adopted. However, the result suffers from image blurring and artifacts. In this article, a tensor-based optimization framework is proposed to exploit more features of the 3-D wall structure and make up for the shortcomings of the 3-D TV algorithm. The 3-D building structure is modeled as a three-order tensor. Just like the 3-D TV algorithm, the local similarity is considered by the TV regularization constraint to guarantee the reconstruction of the edge. Besides, the group sparsity of the structure is considered to suppress the effect of artifacts and blur. Moreover, in order to keep the global correlation of the image in the case of the errors, the tensor Tucker decomposition is adopted. The performance of this method is discussed in the simulation and real radar data results. It shows that the artifacts and blur are suppressed effectively and the 3-D structure is kept as well.